2015
DOI: 10.1080/02699931.2015.1092420
|View full text |Cite
|
Sign up to set email alerts
|

Lonely adolescents exhibit heightened sensitivity for facial cues of emotion

Abstract: Contradicting evidence exists regarding the link between loneliness and sensitivity to facial cues of emotion, as loneliness has been related to better but also to worse performance on facial emotion recognition tasks. This study aims to contribute to this debate and extends previous work by (a) focusing on both accuracy and sensitivity to detecting positive and negative expressions, (b) controlling for depressive symptoms and social anxiety, and (c) using an advanced emotion recognition task with videos of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 28 publications
(34 reference statements)
4
48
1
Order By: Relevance
“…In addition, AVPR1A (Avinun et al., ) has also been associated with prosocial behavior. These previously associated traits are more or less distally related to loneliness, that is, a diminished capacity for emotion recognition could lead to less adequate behavioral reactions during social interactions, with the risk of increasing loneliness (Vanhalst et al., ; Woodhouse et al., ). Again, although showing only weak evidence for involvement of the AVPR1A gene in loneliness, there is suggestive evidence that this gene may modulate precursors of loneliness and could be explored in greater depth in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, AVPR1A (Avinun et al., ) has also been associated with prosocial behavior. These previously associated traits are more or less distally related to loneliness, that is, a diminished capacity for emotion recognition could lead to less adequate behavioral reactions during social interactions, with the risk of increasing loneliness (Vanhalst et al., ; Woodhouse et al., ). Again, although showing only weak evidence for involvement of the AVPR1A gene in loneliness, there is suggestive evidence that this gene may modulate precursors of loneliness and could be explored in greater depth in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The OXT gene has been associated with social withdrawal in children (Francis et al., ) and epigenetic modification of OXT revealed associations with adult attachment style and recognition of emotional faces (Haas et al., ). These alternate phenotypes have all been found to be related to loneliness to a greater or lesser extent (Boivin & Hymel, ; Cassidy & Asher, ; Davis, ; Gardner, Pickett, Jefferis, & Knowles, ; Renshaw & Brown, ; Rubin, Chen, McDougall, Bowker, & McKinnon, ; Vanhalst, Gibb, & Prinstein, ; Zysberg, ). It is evident that attachment styles and social withdrawal tendencies are closely related to loneliness, but the other phenotypes are also related to loneliness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further it is significantly associated with greater sensitivity to 2 main emotions, sadness and fear such that the lonely are more vigilant toward facial cues related to negative emotions [13]. Cultural differences in the experience of loneliness have recently been found.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, accuracy at identifying negative emotions and sensitivity towards negative emotions in faces has been examined. Studies exploring emotion recognition of negative vs. positive emotions showed that lonely adolescents were quicker to correctly identify sad and fearful emotional faces when completing an emotional recognition task that used video footage (Vanhalst, Gibb & Prinstein, ), and accurately recognized angry faces during emotional recognition tasks (Lodder, Scholte, Goossens, Engels & Verhagen, ); both studies found that loneliness was not related to the accuracy or sensitivity towards positive emotions. Spithoven, Bijttebier and Goossens (), in their recent review of loneliness and cognitive processes note that those results are in line with the evolutionary theory of loneliness (Cacioppo and Hawkley, ; Qualter et al ., ) that posits loneliness is related to increased recognition and sensitivity for negative emotions.…”
Section: Introductionmentioning
confidence: 99%